Heavy vehicles and roads technology, safety and policy - Cebon, David; Mitchell, C.G.B (T. Telford, 1992)
Looks at the civil engineering and mechanical engineering aspects of the heavy vehicle/infrastructure system. The state of the art in research and implementation on issues such as highway geometry, traffic management, enforcement technologies and safety are reviewed